Effects of climate and human activity on the current distribution of amphibians in China. Issue 6 (24th August 2022) - Mi, Chunrong; Huettmann, Falk; Li, Xinhai; Jiang, Zhongwen; Du, Weiguo; Sun, Baojun
Abstract: In China, as elsewhere, amphibians are highly endangered. Anthropogenic environmental change has affected the distribution and population dynamics of species, and species distributions at a broad scale are strongly driven by climate and species' ability to disperse. Yet, current knowledge remains limited on how widespread human activity affects the distribution patterns of amphibians in China and whether this effect extends beyond climate. We compiled a relatively comprehensive database on the distribution of 196 amphibian species in China from the literature, public databases, and field data. We obtained 25, 826 records on almost 50% of known species in China. To test how environmental factors and human activities influence the current distribution of amphibians (1960–1990), we used range filling, which is species realized ranges relative to their potential climate distribution. We used all species occurrence records to represent realized range and niche models to predict potential distribution range. To reduce uncertainty, we used 3 regression methods (beta regression, generalized boosted regression models, and random forest) to test the associations of species range filling with human activity, climate, topography, and range size. The results of the 3 approaches were consistent. At the species level, mean annual precipitation (climate) had the most effect on spatial distribution pattern of amphibians in China, followed by range size. Human activity ranked last. At the spatial level, mean annual precipitation remained the most important factor. Regions in southeastern of China that are currently moist supported the highest amphibian diversity, but were predicted to experience a decline in precipitation under climate change scenarios. Consequently, the distributions of amphibians will likely shift to the northwest in the future, which could affect future conservation efforts. Resumen: En China, como en todos lados, los anfibios están gravemente en peligro. El cambio ambiental antropogénico ha afectado la distribución y dinámica poblacional de especies, y la distribución de especies a gran escala están muy influidas por el clima y la habilidad de dispersión de las especies. Sin embargo, el conocimiento actual sigue siendo limitado sobre cómo la actividad humana generalizada afecta a los patrones de distribución de anfibios en China y si este efecto se extiende más allá del clima. A partir de literatura, bases de datos públicas y datos de campo, integramos una base datos relativamente completa sobre la distribución de 196 especies de anfibios en China. Obtuvimos 25, 826 registros de casi 50% de las especies conocidas en China. Para probar cómo los factores ambientales y las actividades humanas influyen en la distribución actual de anfibios (1960‐1990), utilizamos la ocupación de rango, que contrasta los rangos de distribución observada de las especies en relación con su distribución climática potencial. Utilizamos los registros de ocurrencia de todas las especies para representar el rango observado y modelos de nicho para predecir el rango de distribución potencial. Para reducir la incertidumbre, utilizamos 3 métodos de regresión (regresión beta, modelos de regresión acelerada generalizada y bosque aleatorio) para probar las asociaciones de la ocupación de rango de especies con la actividad humana, clima, topografía y extensión de rango. Los resultados de los tres métodos fueron consistentes. A nivel de especie, la precipitación media anual (clima) tuvo el mayor efecto sobre el patrón de distribución de anfibios en China, seguida por la extensión del rango. La actividad humana ocupó el último lugar. A nivel espacial, la precipitación media anual siguió como el factor más importante. Las regiones en el sureste de China que aun son húmedas sostuvieron la mayor diversidad de anfibios, pero se pronosticó que la precipitación declinará bajo escenarios de cambio climático. Consecuentemente, la distribución de anfibios muy probablemente cambiará hacia el noreste, lo cual podría afectar esfuerzos futuros de conservación. 摘要: 两栖动物是陆生脊椎中最受胁的类群, 中国两栖动物的受胁状态更为严峻。人类活动导致的环境变化深刻影响着物种的分布和种群动态。传统生态学认为大尺度上的物种分布格局主要受当前气候和物种扩散能力的影响。近几百年来, 人类活动的日益加剧, 其对物种分布的影响也日益加强。中国幅员辽阔, 自然环境类型多样, 同时人口众多。然而, 目前尚不知自然因素和人类活动是如何影响着中国两栖动物当前的分布格局？人类活动的影响是否已经超出了气候等自然环境因素的影响？我们通过三种方法收集了中国两栖动物的分布数据, 包括615篇文献, 网上公开数据和野外调查数据, 最终获得中国196种两栖动物的25826个分布点。并将这些数据用于预测两栖动物当前潜在分布区, 用实际分布点代表其当前实际分布区, 实际分布区和潜在分布区的比值来代表每一物种对其潜在分布区的占据状态。为了减少不确定性, 我们使用了三种回归模型 (beta 回归、广义增强回归模型和随机森林), 在物种尺度和地理空间尺度上分析人类活动因子 (人口密度、人类足迹、农田比例), 气候因子 (年均温、年均降水量, 古气候变化), 以及物种分布的海拔范围和分布区大小等因素对当前中国两栖动物分布占据的影响。三种回归方法的结果一致。在物种尺度, 降水是影响中国两栖动物空间分布格局的最重要因素, 其次是物种的分布范围。生活在湿润区域以及分布面积大的物种其占据潜在适宜栖息地的比例更高。人类活动的影响尚不明显。在地理空间尺度, 降水依然是影响中国两栖动物当前分布格局的最重要因子。分布占据高的区域在中国的东南部, 这和中国当前的降水空间分布格局一致。中国的东南部是两栖动物多样性最高的区域之一, 但预计在气候变化情景下降水量将减少。因此, 未来这些区域的两栖动物很可能向西北方向迁移, 这将影响未来的生物多样性保护。